A Porcine circovirus type 2b (PCV2b)-based experimental vaccine is effective in the PCV2b-Mycoplasma hyopneumoniae coinfection pig model. Issue 44 (16th October 2019) - Opriessnig, Tanja; Castro, Alessandra M.M.G.; Karuppanan, Anbu K.; Gauger, Phillip C.; Halbur, Patrick G.; Matzinger, Shannon R.; Meng, Xiang-Jin
Abstract: Porcine circovirus type 2 (PCV2) is one of the major swine pathogens causing high economic losses due to PCV2-associated disease (PCVAD). PCV2 infection is not only immunosuppressive by damaging lymphoid tissues but is also exacerbated by co-infections with other pathogens including Mycoplasma hyopneumoniae . While PCV2 can be divided into several genotypes, currently only PCV2a, PCV2b and PCV2d are globally prevalent and considered of major importance. Most commercial PCV2 vaccines are based on PCV2a isolates; however, the high prevalence of PCV2b and PCV2d in the global pig population is raising concerns among pig veterinarians. The objective of this study was to evaluate the efficacy of an experimental PCV2b-based subunit vaccine in a combined PCV2b and M. hyopneumoniae coinfection model. Briefly, a total of 49 PCV2- and M. hyopneumoniae -free 3-week-old pigs were randomly divided into four groups: A non-vaccinated, non-infected NEG-CONTROL group, a non-vaccinated, PCV2b-infected, POS-CONTROL group, and two vaccinated and PCV2b-infected groups (SINGLE-VAC, DUAL-VAC). SINGLE-VAC and DUAL-VAC pigs were vaccinated at 3 weeks of age and DUAL-VAC pigs received a booster dose at 5 weeks of age. All pigs, except NEG-CONTROLs, were experimentally infected with M. hyopneumoniae 28 days after initial vaccination and challenged with PCV2b one week later. The pigs were necropsied 21 days after PCV2b challenge. Prior to PCV2b challenge, both vaccinated groups had detectable humoral and cell-medicated immune responses to PCV2. Vaccination significantly reduced PCV2b viremia and also reduced or eliminated PCV2-associated lymphoid lesions compared to the POS-CONTROL pigs. Under the study conditions, an experimental PCV2b vaccine protected conventional growing pigs against PCV2b viremia and associated lesions in a coinfection model with some advantages of the two-dose regimen versus the one dose regimen. Both protocols induced neutralizing antibodies against PCV2a and PCV2d prior to challenge.